Batik Ecoprint Berbahan Dasar Daun Jati Sebagai Pengenalan Nilai-Nilai Budaya Madura - Shinta Oktafiana (Prosiding Temu Ilmiah Nasional Guru, 2022)
The application of the independent learning curriculum contains various aspects of development, especially in the project of strengthening the Pancasila profile where students must be able to instill the Pancasila character, one of which is preserving the surrounding culture. The purpose of this study was to find out the process of making ecoprint batik with fire-based materials, to find out the student's response to the activity and also to know the response of the related early grade parents. This research method uses descriptive quantitative carried out in all public elementary schools in Tlanakan sub-district totaling 33 schools. The object of this research is all 55 teachers of elementary schools in Tlanakan sub-district. The selection of grade 1 teachers was due to the application of the independent curriculum in grades 1 and 4 while those who carried out ecoprint batik were only in grade 1. The research sample used a saturated sample in which the entire population was used as the object of research because the number was small. The results of the research are 1) the process of making ecoprint batik without the element of fire is very easy and the selection of teak leaves as the basic material as it is easy to find according to 53 statements, and as many as 52 states the color is better 2) there are four cultural values that appear in batik activities This is the value of politeness with an average of 13.91, deliberation with an average of 13.47, mutual cooperation with an average of 13.00 and love of local products of 12.35.